Effects of running speeds on some markers of muscular tissues and synovial fluid of Iraqi Arabian Horses: Amir I. Towfik1; Heifa´a J. Hassan2 and Basima J. Mohamed2 - Towfik, Amir I. (The Iraqi Journal of Veterinary Medicine, 2018)
Arabian horses are regarded as the most famous breed for speed for long distances due to their genetic superiority. The aims of the study were to focus on the effect of different running speeds on the muscular tissues (Myoglobin, creatine kinase, aspartate transaminase), lactate dehydrogenase and synovial fluid (creatine kinase, aspartate transaminase and lactate dehydrogenase). Non-trained eight local Iraqi Arabian horses were run on soil track for a distance (1) Km, walking, trot, canter, and gallop. Blood and synovial fluid samples were collected before and after running. The biochemical parameters of serum showed gradual increase according to each type of speed. All of them were significant at P≤0.01. The biochemical parameters of the synovial fluid also showed gradual increase according to each type of speed. Creatine kinase was significant at P≤0.05 in walking and trot but significant at P≤0.01 in canter and non-significant in gallop. While aspartate transaminase, and lactate dehydrogenase were significant at P≤0.01 at all speeds.